Relationship between upper body strength and performance at canoe freestyle - Csonková, N.; Kutlík, D. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2017)
Performance in all canoe disciplines is based on the physical condition of the paddler and his technique and mental ability to adapt to the racing condition. The strength belongs to the most important physical factors in canoe sprint and canoe slalom disciplines. We believed that in canoe freestyle the strength has an important role in relation to the performance in comparison to other canoe disciplines. The aim of this study was to identify the relationship between upper body strength and special canoe freestyle performance. The study group consisted of 16 senior kayak freestyle paddlers in the age group 26 ± 3 years old. Fitro Dyne Premium was device used to obtain data for analysis of the level of general upper body strength abilities. To determine special upper body strength we used tests on paddle machine and freestyle kayaking flat water tests. Freestyle performance was measured during ECA Euro Cup 2013 competition in Slovakia, Cunovo by official ICF judges. The data obtained were measured by the Spearman Correlation (r) correlation test. The results of the study show significant relations between kayak freestyle performance and test of general strength endurance (p < 0.05), special strength endurance, special dynamic strength (p < 0.01). There were no statistically significant correlations between kayak freestyle performance and general maximal power, dynamic strength, special maximal power.